Risk terrain modeling for road safety: identifying crash-related environmental factors in the province of Cádiz, Spain - Giménez-Santana, Alejandro (European journal on criminal policy and research, 2018)
Environmental Criminology has developed a robust framework that provides the scientific support and necessary foundation for crime analysis through crime mapping. This theoretical approach focuses on the situational and temporal characteristics of criminal opportunity rather than on the offender’s behavior for crime prevention. In the scope of road safety and traffic crashes, few studies have adopted this approach. This study used risk terrain modeling (RTM), developed by the Rutgers Center on Public Security, to determine the relative importance of varying environmental risk factors on alcohol-related crashes and traffic accidents. The independent variables consisted of a set of potential environmental risk factors, while the dependent variable comprised all DWI crashes and traffic accidents in the province of Cádiz in 2012. According to the results of the current study, restaurant locations are spatially associated with the occurrence of drunk driving crashes, while proximity restaurants and recreational lodging centers correlate with the sites of traffic accidents.